The Shift from Paradiplomacy to Protodiplomacy: A Comparative Study of Catalonia and Kurdistan - Adistia, Margaretha Novianti; Fidriansyah, Muhammad Anugrah; Utami, Rizka Yeza; Yanti, Nofi; Krisnadi, Muhammad Faiz (Universitas Muhammadiyah Yogyakarta, 2024)
This article explored the transition from paradiplomacy to protodiplomacy in Catalonia and Kurdistan, two regions at the forefront of this shift. Protodiplomacy involves the direct participation of subnational entities in diplomatic activities akin to those of recognized nation-states, challenging traditional diplomatic hierarchies and altering the global diplomatic landscape. Catalonia has greater autonomy in matters such as governance and economy, while Kurdistan has more limited autonomy in matters such as security and governance. As such, this research showed that paradiplomacy could serve as a means to increase regional engagement in international politics. This research provided an in-depth analysis of how the South Sulawesi Provincial Government's paradiplomacy initiative impacts the export of agricultural products to Egypt. Through a comparative analysis of Catalonia and Kurdistan, this study elucidated the motivations, consequences, and challenges associated with this transition. It emphasized the significance of effective paradiplomacy practices between central and local governments. Catalonia and Iraqi Kurdistan exemplified modern paradiplomacy, showcasing their capabilities on an international stage. The research identified high Iraqi Kurdish nationalism as a key driver of the shift towards protodiplomacy in Kurdistan. It also highlighted the internal structural factors within Iraq that propelled Iraqi Kurdistan's diplomatic efforts, culminating in a referendum that marked a peak in separatist interest. This research underscored the dynamic nature of protodiplomacy, highlighting the motivations behind subnational diplomatic endeavors and the transformative implications for central-local government relations.